Trace element chemistry and U–Pb dating of zircons from oceanic gabbros and their relationship with whole rock composition (Lanzo, Italian Alps) - Kaczmarek, Mary-Alix; Muentener, O.; Rubatto, D. (Springer, 2008)
Contributions to Mineralogy and Petrology